Implementation of The Plantation Production Sharing Agreement in The Unwritten Agreement Form - Teng Berlianty; Yosia Hetharie; Ronald Saija (Jambura Law Review, 2022)
This study aims to identify and analyze the implementation of the plantation production sharing agreement in Nalahia Village, Central Maluku. This research is a sociolegal research, which is a combination research method between doctrinal law research methods and empirical legal research methods. This research was conducted in Nalahia Village, Nusalaut District, Central Maluku, with the sample being the people of Nalahia Village who had implemented a plantation production sharing agreement. This type of research data is primary data and secondary data obtained through literature study and interviews. Based on the results of the research, the agreement for plantation production in Nalahia Village, Maluku is carried out according to the habits of the Nalahia people since the time of the ancestors in an unwritten form between the plantation owner and the sharecropper based on mutual trust that is attached and is still maintained to this day. The owners of the plantations are the indigenous people of Nalahia Village, while the sharecroppers are mostly not indigenous people but live and settle in Nalahia. This plantation production sharing agreement was agreed with the percentage of the distribution of the plantation products was 50: 50. although at this time, the percentage of the distribution could be different according to the agreement of both parties. The implementation of this plantation production sharing agreement will end with the completion of the smallholders harvesting the plantation products belonging to the hamlet owners.